The Effect of Brine on the Electrical Properties of Methane Hydrate. Issue 11 (6th November 2019) - Lu, R.; Stern, L. A.; Du Frane, W. L.; Pinkston, J. C.; Roberts, J. J.; Constable, S.
Abstract: Gas hydrates possess lower electrical conductivity (inverse of resistivity) than either seawater or ice, but higher than clastic silts and sands, such that electromagnetic methods can be employed to help identify their natural formation in marine and permafrost environments. Controlled laboratory studies offer a means to isolate and quantify the effects of changing individual components within gas‐hydrate‐bearing systems, in turn yielding insight into the behavior of natural systems. Here we investigate the electrical properties of polycrystalline methane hydrate with ≥25% gas‐filled porosity and in mixture with brine. Initially, pure methane hydrate was synthesized from H2 O ice and CH4 gas while undergoing electrical impedance measurement, then partially dissociated to assess the effects of pure pore water accumulation on electrical conductivity. Methane hydrate + brine mixtures were then formed by either adding NaCl (0.25–2.5 wt %) to high‐purity ice or by using frozen seawater as a reactant. Conductivity was obtained from impedance measurements made in situ throughout synthesis while temperature cycled between +15 °C and −25 °C. Several possible conduction mechanisms were subsequently determined using equivalent circuit modeling. Samples with low NaCl concentration show a doping/impurity effect and a log linear conductivity response as a function of temperature. For higher salt content samples, conductivity increases exponentially with temperature and the log linear relationship no longer holds; instead, we observe phase changes within the samples that follow NaCl–H2 O–CH4 phase equilibrium predictions. Final samples were quenched in liquid nitrogen and imaged by cryogenic scanning electron microscopy (cryo‐SEM) to assess grain‐scale characteristics. Key Points: Electrical properties of a multicomponent methane hydrate system synthesized from a mixture of ice, NaCl, and CH4 gas were examined Electrical conductivity of samples increases nonlinearly with increasing salt content for temperatures above −15 °C No secondary NaCl‐bearing phases were detected in samples with <1.0 wt % salt due to possible incorporation into the hydrate structure